The Effect of Confluence Angle on the Flow Pattern at a Rectangular Open-Channel - Rooniyan, F. (Engineering, Technology & Applied Science Research, 2014)
Flow connection in channels is a phenomenon which frequently happens in rivers, water and drainage channels and urban sewage systems. The phenomenon appears to be more complex in rivers than in channels, especially at the y-junction bed joint that causes erosion and sedimentation at some areas resulting to morphological changes. Flow behavior at the channel junction area depends on variables such as channel geometry, discharge ratio, tributary width and y-junction connection angle of the channel, bed level changes at the bed joint, flow characteristic at the bed joint upstream and flow Froude number in different sections. In this research, fluent numerical model and junction angles of 30o, 45o & 60o are used to analyze and evaluate the effect of channel junction geometry on the flow pattern and the flow separation zone dimensions in different ratios of flow discharge (upstream channel discharge to total discharge of the flow). Results for two ratios of flow discharge are represented. Results are in agreement with earlier studies and it is shown that the change of the channel crossing angle affects the flow pattern in the main channel and also that the dimensions of the created separation zone in the main channel become larger when the crossing angle increases. This phenomenon can also be observed when the flow discharge ratio is lower. Analysis showed that the least dimension of the separation zone will be at the crossing angle of 45o .